Revisiting the role of charismatic communities in the Philippine Catholic Church - Bustamante, Pauline Mary C. (Animo Repository, 2019)
Does joining a charismatic community create division in the Catholic Church? This has been one of the main historical issues of the charismatic movement in the Philippines. In the past, some have strongly argued that charismatic groups are creating division with the local parishes since parishioners would rather attend prayer meetings instead of being in church. Through a critical analysis and reflection, this paper wishes to re-affirm the relevant role of charismatic movements in nourishing individuals and communities that might not have been reached by the parishes. Over the last 40-50 years since the birth of Catholic charismatic communities, these have been true multipliers in spreading the Gospel of love and mercy to the unchurch and inactive parishioners.